The Role of Islamic Boarding Schools in Shaping the Character of Santri - Ummah, Nafisatul; Arifin, M. Zainal; Asy`ari, Hasyim (International Journal on Advanced Science, Education, and Religion, 2025)
Character education has emerged as a significant and widely discussed topic in recent years, drawing considerable attention from educators and researchers alike. Many studies have explored its relationship with the roles played by educators and educational institutions. In this context, the contribution of Islamic boarding schools (pesantren) to character development, particularly in the era of disruption, remains an important area of inquiry. However, existing research has yet to comprehensively address how pesantren actively shape national character. This study seeks to fill that gap by examining the role of character education in the Al-Quranyy Islamic Boarding School. Specifically, it aims to: (1) explore how character education is implemented among students at Al-Quranyy Islamic Boarding School, and (2) identify the supporting and inhibiting factors affecting its implementation. Employing a qualitative field research approach, the study reveals that character formation at Al-Quranyy is facilitated through both instructional content and the exemplary behavior of kyai, dormitory caregivers, and teachers. Furthermore, character education is reinforced through pesantren programs such as extracurricular and local content activities. The study also identifies several challenges and supports in this process: internally, a lack of infrastructure and teaching personnel; externally, the pervasive influence of technological developments.